Uso de películas comestíveis e gelatina na conservação de frutos de mini tomate orgânico 'Sweet Grape' - Evangelista, Regina Marta [UNESP]; Gouveia, Aline Mendes de Sousa [UNESP]; Corrêa, Carla Verônica [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (My University, 2014)
The objective of this Trial was to evaluate post harvesting quality of fruits of organic mini tomatoes ‘Sweet Grape’ submitted to different edible coatings application associated with gelatin. Five treatments were evaluated, consisting of different edible coatings application on fruits: control (immersion in water deionized), cassava starch at 3% + gelatin at 10% (FM3% + G10%); potato starch at 3% + gelatin at 10% (FB3% + G10%); corn starch at 3% + gelatin at 10% (AM3% + G10%) and gelatin at 10% (G10%). Fruits were refrigerated for 3 minutes and immersed in the solutions, that was at 30ºC for 1 minute. After drying at environment, they were put in trays of expanded polystyrene and stored in cold chamber at 10±2 ºC and 89±2% of relative humidity, during 14 days. Evaluations were made weekly (0, 7and 14 days). It was observed increasing in ascorbic acid content in fruits stored for 14 days. Treatment FB3% + G10% resulted in lesser soluble solids content in evaluations made a 0 and 7 days. However, besides the edible coatings used in this trial did not reduce water loss, they maintained the fruit quality, mainly texture and reducing sugars.

Objetivou-se com este trabalho avaliar a qualidade pós-colheita de frutos de mini tomates orgânicos ‘Sweet Grape’ submetidos a diferentes aplicações de películas comestíveis associadas à gelatina sem sabor, incolor (Royal®). Foram avaliados cinco tratamentos, que consistiram de diferentes aplicações de películas comestíveis sobre os frutos: controle (imersão em água deionizada); fécula de mandioca a 3% + gelatina a 10% (FM3% +G10%); fécula de batata 3% + gelatina a 10% (FB3% + G10%); amido de milho 3% + gelatina 10% (AM3% +G10%) e gelatina a 10% (G10%). Os frutos foram refrigerados por 3 minutos e imersos nas soluções, que estavam a 30 ºC, por 1 minuto. Após a secagem no ambiente, foram colocados em bandeja de poliestireno expandido e armazenados em câmara fria em temperatura de 10±2 ºC e 89±2% de umidade relativa, durante 14dias. As avaliações foram realizadas semanalmente (0, 7 e 14 dias). Observou-se aumento nos teores de ácidoas córbico nos frutos armazenados por 14 dias. O tratamento FB3% + G10% apresentou menores valores desólidos solúveis nas avaliações realizadas aos 0 e 7 dias. No entanto, apesar das películas comestíveis utilizadas neste trabalho não terem diminuído a perda de água, mantiveram a qualidade dos frutos, principalmente textura e açúcares redutores.
Edible coatings and gelatin in conservation of fruits of organic mini tomato ‘Sweet Grape’
Keywords: Solanum lycopersicun; Post-harvesting quality; Starch; Solanum lycopersicun; Qualidade pós-colheita; Amido